PROPOSITION D’UN SYSTEME EXPERT D’ANALYSE DES DONNEES DES PATIENTS DANS UN LABORATOIRE MEDICALE, CAS DU LABORATOIRE DES CLINIQUES UNIVERSITAIRES DE L’UELE DANS LA VILLE D’ISIRO - Makimi Ngeme Patrick, (IJRDO -Journal of Computer Science Engineering, 2024)
Nowadays, ICTs passing by Expert Systems and Artifical Intelligence provide several amazing possibilities in automatic interpretation of medical objectives in analyses done in laboratory. This technology can be efficient.